Death and end times: the effects of religious fundamentalism and mortality salience on apocalyptic beliefs. Issue 1 (2nd January 2018) - Routledge, Clay; Abeyta, Andrew A.; Roylance, Christina
ABSTRACT: According to terror management theory, the awareness of death motivates people to subscribe to cultural worldviews that offer some form of death transcendence. In support of this assertion, studies reveal that stimuli that heighten the awareness of death (mortality salience) increase investment in and defense of cultural worldviews (e.g., religion). Although past research has elucidated different forms of mortality salience-induced religious worldview defense, no study to date has considered how death-awareness contributes to apocalyptic beliefs derived from religious prophecy. The present research indicates that individual differences in religious fundamentalism interact with mortality salience to influence religious apocalyptic beliefs. For people higher in religious fundamentalism, mortality salience increased apocalyptic beliefs. For people lower in religious fundamentalism, mortality salience decreased apocalyptic beliefs.